Speciation and source changes of atmospheric arsenic in Qingdao from 2016 to 2020 - Response to control policies in China. (February 2023) - Sun, Haolin; Wang, Yan; Liu, Ruhai; Yin, Pingping; Li, Dou; Shao, Long
Abstract: Arsenic (As) is a toxic pollutant in the atmosphere. The atmospheric As concentration is high over the East Asian continent. At present, there is less research on the long-term trend of atmospheric arsenic pollution, which is not conducive to understanding its behavior. Total suspended particulate matter (TSP) samples were collected in Qingdao in autumn and winter from 2016 to 2020 to analyze total arsenic (TAs), As(V) and As(III). The interannual variation patterns, influencing factors and health risks of arsenic concentrations in aerosols were discussed. The results showed that As(V) is the dominant species of arsenic in aerosols. The average concentration of TAs gradually decreased and the proportion of As(III) increased during autumn and winter from 2016 to 2020. The levels of TAs, As(V) and As(III) in aerosols increased during the heating period and on polluted days. Negative correlation between TAs/TSP and TSP indicated that higher concentrations of TSP in the atmosphere would reduce the content of TAs in particulate matter. The increase of secondary aerosol particles played a dilution effect. Mobile source emissions, biomass and coal combustion were main sources of atmospheric arsenic. The distribution range of large potential sources of atmospheric arsenic decreased from 2016 to 2020, and concentrated, mainly in parts of Shandong province and its offshore areas. Local sources contributed the most to atmospheric arsenic pollution in Qingdao in autumn and winter. TAs, As(V) and As(III) posed a low non-carcinogenic risk and a negligible carcinogenic risk to adults and children. This study reveals the influence of strict air pollution control policies on the speciation and source of arsenic in aerosols. Graphical abstract: Image 1 Highlights: TAs and its species decreased but As(III)/TAs increased from 2016 to 2020. TAs, As(V), As(III) and As(III)/TAs increased during the heating period and polluted days. Main potential source areas of atmospheric arsenic were reduced and concentrated. Non-carcinogenic and carcinogenic risks of TAs, As(V) and As(III) were small and decreased.